2022
DOI: 10.1080/19490976.2022.2105609
|View full text |Cite
|
Sign up to set email alerts
|

Gut microbiota-derived metabolites confer protection against SARS-CoV-2 infection

Abstract: The gut microbiome is intricately coupled with immune regulation and metabolism, but its role in Coronavirus Disease 2019 (COVID-19) is not fully understood. Severe and fatal COVID-19 is characterized by poor anti-viral immunity and hypercoagulation, particularly in males. Here, we define multiple pathways by which the gut microbiome protects mammalian hosts from SARS-CoV-2 intranasal infection, both locally and systemically, via production of short-chain fatty acids (SCFAs). SCFAs reduced viral burdens in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 72 publications
0
21
0
Order By: Relevance
“…Other applications include exploring the thanatomicrobiome, in determining the time elapsed since microbial death [ 56 ]. Further applications include tracking the microbiome before and after exposure to diseases like SARS COV2 [ 57 ], and determining changes in the microibial composition following dietary alterations [ 58 , 59 , 60 ].…”
Section: Discussionmentioning
confidence: 99%
“…Other applications include exploring the thanatomicrobiome, in determining the time elapsed since microbial death [ 56 ]. Further applications include tracking the microbiome before and after exposure to diseases like SARS COV2 [ 57 ], and determining changes in the microibial composition following dietary alterations [ 58 , 59 , 60 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, SCFAs boost adaptive immunity through GPCR (GPR41 and GPR43) signaling. Together, these results have shown unexpected roles for SCFAs in preventing hypercoagulation and viral entry while enhancing adaptive antiviral immunity …”
Section: Role Of Scfas In Sars-cov-2 Therapeuticsmentioning
confidence: 94%
“…From these analyses, it is anticipated that altered microbiomes may affect the outcome of acute COVID infection and may be involved in long-COVID sequelae. More recently, one group demonstrated that treatments with a high-fiber diet containing pectin and/or with mix of SCFAs in the drinking water were both able to reduce the levels of SARS-COV-2 entry receptor angiotensin-converting enzyme 2 (ACE2) and, therefore, to reduce viral burdens in intranasal infection model using mice and hamsters ( 139 ). According to this study, treatments also increased immune adaptive responses via activation of FFAR2 and FFAR3 (but only in males), and reduced coagulation and platelet turnover by regulating the Sh2b3-Mpl axis ( 139 ).…”
Section: Effects Of Butyrate In Distinct Respiratory Diseasementioning
confidence: 99%
“…More recently, one group demonstrated that treatments with a high-fiber diet containing pectin and/or with mix of SCFAs in the drinking water were both able to reduce the levels of SARS-COV-2 entry receptor angiotensin-converting enzyme 2 (ACE2) and, therefore, to reduce viral burdens in intranasal infection model using mice and hamsters ( 139 ). According to this study, treatments also increased immune adaptive responses via activation of FFAR2 and FFAR3 (but only in males), and reduced coagulation and platelet turnover by regulating the Sh2b3-Mpl axis ( 139 ). In this context, in depth analyses of metabolites including SCFAs may emerge a potential new therapeutic in the current and future pandemic.…”
Section: Effects Of Butyrate In Distinct Respiratory Diseasementioning
confidence: 99%